1992
DOI: 10.1152/jappl.1992.72.5.1818
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen cost of exercise hyperpnea: implications for performance

Abstract: We addressed two questions concerned with the metabolic cost and performance of respiratory muscles in healthy young subjects during exercise: 1) does exercise hyperpnea ever attain a "critical useful level"? and 2) is the work of breathing (WV) at maximum O2 uptake (VO2max) fatiguing to the respiratory muscles? During progressive exercise to maximum, we measured tidal expiratory flow-volume and transpulmonary pressure- (Ptp) volume loops. At rest, subjects mimicked their maximum and moderate exercise Ptp-volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
235
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(258 citation statements)
references
References 17 publications
18
235
1
4
Order By: Relevance
“…To meet these ventilatory requirements the respiratory muscles require a substantial blood flow and O 2 supply. Data in highly fit subjects suggest that up to 16% of the total V O 2 max and total cardiac output is devoted to inspiratory and expiratory muscles during maximum exercise (3,40). These indirect estimates agree closely with those in running equines as measured directly with radiolabeled microspheres (75,76).…”
Section: Exercise Demands On the Respiratory Musclessupporting
confidence: 69%
“…To meet these ventilatory requirements the respiratory muscles require a substantial blood flow and O 2 supply. Data in highly fit subjects suggest that up to 16% of the total V O 2 max and total cardiac output is devoted to inspiratory and expiratory muscles during maximum exercise (3,40). These indirect estimates agree closely with those in running equines as measured directly with radiolabeled microspheres (75,76).…”
Section: Exercise Demands On the Respiratory Musclessupporting
confidence: 69%
“…1 However, mask-induced respiratory changes remain central in the explanations for impaired exercise performance during mask wear in the studies discussed above. First, an obvious difference between mask wear and non-wear is respiratory dead space.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this concept, Aaron et al [35] observed that the oxygen cost of breathing increases to 15% of total oxygen consumption in the presence of severe expiratory airflow limitation.…”
Section: Increased Work and Oxygen Cost Of Respiratory Musclesmentioning
confidence: 93%
“…During exercise in healthy subjects, the oxygen consumption of respiratory muscles accounts for 5-10% of whole body oxygen consumption [35]. However, alterations in EELV, ventilation-perfusion ratio and airway calibre alter the work, and therefore oxygen consumption of the respiratory muscles [36].…”
Section: Increased Work and Oxygen Cost Of Respiratory Musclesmentioning
confidence: 99%